A CLINICAL SURVEY OF VIRAL RESPIRATORY DISEASES OF COMMERCIAL POULTRY IN PAKISTAN - M. Usman; F. Sarwar; S. Umar; S. Subhan; M. L. Sohail; M. Younus; M. A. Shah (Journal of Animal and Plant Sciences, 2017)
Viral diseases are a huge concern for poultry farmers in Pakistan since 1963. Multiple common viral respiratory diseases (CVRDs) such as, infectious bronchitis (IB), newcastle disease (ND), swollen head syndrome (SHS) and low pathogenic avian influenza (LPAI) cause huge economic losses in poultry industry. Incidence rates of CVRDs are not reported in various developing countries including Pakistan. A survey of CVRDs based on clinical diagnosis was carried out in Pakistan. Diagnostic laboratories provided the data of viral diseases affecting respiratory system in different types of chicken flocks, during different seasons in different regions. This survey suggested that ND is the most prevalent disease followed by IB, LPAI and the least prevalent was SHS. The information presented here are of great value in the research, prevention, and control of poultry diseases.
Keywords: viral respiratory diseases; chicken; survey; Pakistan